Public Value-Oriented Governance in the Digital Era: Strategies to Overcome the Crisis of Citizens' Trust in the Government in Indonesia - Rira Nuradhawati; Imanda Setyawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Abstract Digital transformation in Indonesia's public sector is promoted as a means of increasing efficiency, transparency, and participation, but gaps in bureaucratic capacity and infrastructure have resulted in uneven results and impacted citizen trust in government. This article analyzes how public value-oriented governance in the digital era can be a strategy to address this crisis of trust. A qualitative approach is used through a literature review of research on policy implementation, e-government, digital transformation, and public trust in Indonesia. The findings indicate that digitalization is often understood as merely technology adoption, while dimensions of public value such as accountability, responsiveness, fair access, and protection of citizen rights have not been systematically integrated. Limited human resource capacity, the digital divide, and weak central-regional coordination exacerbate service disparities and reinforce perceptions of injustice. On the other hand, good practices such as digital transformation roadmaps, strengthening data culture, and transformational leadership demonstrate the potential to improve service quality and public perception when linked to the goal of creating public value, rather than simply administrative efficiency. This article proposes a strategic framework that includes: (1) sharpening the public value vision in government digital policies; (2) strengthening data governance and transparency; (3) increasing transformational digital capacity and leadership; and (4) expanding citizen participation and rights protection in the digital space. The theoretical implication is the need to integrate the concepts of public value and digital governance; practically, this research emphasizes that restoring citizen trust is only possible if digital innovation is accompanied by inclusive, rights-based, and accountable governance reforms. Keywords: public value, e-government, digital transformation, governance, public trust, Indonesia.